Effect of process parameters on convective heat transfer coefficient of fluid and heat partitioning in high efficiency deep grinding with water-based coolant - Vashista M.; Paul S. (My University, 2025)
A statistical analysis was undertaken to study the role of process parameters on the convective heat transfer coefficient of fluid (hf) and heat partitioning ratios in HEDG. Heat partitioning ratios have been calculated by using experimental data and models developed by previous researchers. Regression models between grinding process parameters and partitioning ratios has been developed using DoE technique and RSM. Heat partitioning ratio to chip increases with MRR and takes around 20% of grinding heat. Very less amount of heat is carried away by workpiece and cubic boron nitride grinding wheel. The hf increases with wheel speed and reduction in contact length. This enables the grinding fluid to take most of heat and limits the rise in temperature upto 140°C despite of high MRR. Previous researchers considered constant value of hf, but in present study variation in hf with process parameters has been considered to calculate the heat portioning ratios. © Copyright 2016 Inderscience Enterprises Ltd.